Genetically Encoded Tools for Research of Cell Signaling and Metabolism under Brain Hypoxia - Alexander I. Kostyuk; Aleksandra D. Kokova; Oleg V. Podgorny; Ilya V. Kelmanson; Elena S. Fetisova; Vsevolod V. Belousov; Dmitry S. Bilan (MDPI AG, 2020)
Hypoxia is characterized by low oxygen content in the tissues. The central nervous system (CNS) is highly vulnerable to a lack of oxygen. Prolonged hypoxia leads to the death of brain cells, which underlies the development of many pathological conditions. Despite the relevance of the topic, different approaches used to study the molecular mechanisms of hypoxia have many limitations. One promising lead is the use of various genetically encoded tools that allow for the observation of intracellular parameters in living systems. In the first part of this review, we provide the classification of oxygen/hypoxia reporters as well as describe other genetically encoded reporters for various metabolic and redox parameters that could be implemented in hypoxia studies. In the second part, we discuss the advantages and disadvantages of the primary hypoxia model systems and highlight inspiring examples of research in which these experimental settings were combined with genetically encoded reporters.